1972
DOI: 10.1128/aem.24.4.535-539.1972
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Detection of Some Food-Borne Bacteria

Abstract: Studies on detection of bacteria by radiometric techniques have been concerned primarily with aerobic species in clinical specimens. The data presented here are related to detection of aerobic and anaerobic species that are of significance in foods, by measurement of "4CO2 evolved from the metabolism of 14Cglucose. Salmonella typhimurium and Staphylococcus aureus were inoculated into tryptic soy broth containing 0.0139 ,gCi of 14C glucose/ml of medium. Detection times ranged from 10 to 3 hr for inocula of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…On the basis of this principle, the instrument, BacT/Alert 3D has been commonly used in hospitals monitoring the sterility and bacterial growth in clinical specimen (Carricajo and others 2001;Krisher and others 2001). Measurement of CO 2 using gas chromatography (Guerzoni and others 1985;Basem and others 1992), radiometric techniques (Previte 1972), and an infrared CO 2 analyzer (Threlkeld 1982;Chew and Hsieh 1998;Hsieh and Hsieh 1998) have all been successful in determining the level of contamination by mesophilic and coliform bacteria in food samples, including hamburger, milk, water, catfish, and bottled juice. Recently, Hsieh and Hsieh (2000) developed a noninstrumental microrespirometer technique that is fast (<2 h), sensitive, and easy to operate.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this principle, the instrument, BacT/Alert 3D has been commonly used in hospitals monitoring the sterility and bacterial growth in clinical specimen (Carricajo and others 2001;Krisher and others 2001). Measurement of CO 2 using gas chromatography (Guerzoni and others 1985;Basem and others 1992), radiometric techniques (Previte 1972), and an infrared CO 2 analyzer (Threlkeld 1982;Chew and Hsieh 1998;Hsieh and Hsieh 1998) have all been successful in determining the level of contamination by mesophilic and coliform bacteria in food samples, including hamburger, milk, water, catfish, and bottled juice. Recently, Hsieh and Hsieh (2000) developed a noninstrumental microrespirometer technique that is fast (<2 h), sensitive, and easy to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been made to shorten length of analysis. These methods include a membrane filter technique (4), radiometric measurements (2,3), and microcalorimetry (2). Recently, changes in electrical impedance taking place in the medium of growing cultures have been used to detect the presence of bacteria (1).…”
mentioning
confidence: 99%
“…The use of a small amount of "IC-labeled medium produces an earlier response than methods involving larger volumes of medium (1, 2, 3, 16,20,21). This large inoculum rapidly poises the medium and initiates growth.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the radiometric method did not provide earlier evidence of bacteremia than did routine proce-dures and that it was impossible to detect 4 to 4,250 colony-forming units (CFU) within 6 h. Deblanc et al (1) compared 2,967 blood cultures by conventional techniques and found that bacteria were detected more rapidly 70% of the time by the radiometric method. Waters (21) and Previte (16), by using an automated radiometric method, reported that detection times for various bacteria decreased with increased cell numbers. Depending upon species, inocula of 100 cells were detected in 6 to 14 h.…”
mentioning
confidence: 99%